Montenegro : Request for Purchase under the Rapid Financing Instrument; Press Release; Staff Report; and Statement by the Executive Director for Montenegro. (IMF Staff Country Reports; Country Report, 2020)
The COVID-19 pandemic will hit Montenegro hard, as tourism is a key industry. Fiscal space has eroded in recent years due to large public capital outlays, and the COVID-19 crisis is creating new budgetary strains as health spending and other expenditures rise, while the economic contraction lowers revenues.